Validity of anthropometric measurements for estimation of obesity among geriatric residing in Bhavnagar city Gujarat, Western India - Trivedi, Bansi Janak; Trivedi, Atul V. (International Journal Of Community Medicine And Public Health, 2022)
Background: Validity of anthropometric measurements has not been adequately evaluated in diverse geriatric population. We determine diagnostic accuracy of body mass index using different anthropometric in assessing the obesity in geriatrics. Methods: This community based cross sectional study was carried out in Bhavnagar city among geriatric people (≥60) residing in 13 different wards of Bhavnagar city during September 2019 to September 2020. Anthropometric data (height, weight, mid upper arm circumference, waist circumference, hip circumference, and skinfold thickness) were measured. Prevalence of obesity measure by different method was compared using kappa coefficient, sensitivity, and specificity. Results: Fair agreement found between waist circumference and BMI for obesity. High sensitivity and low specificity found for BMI measurements at the cut off 30 kg/m2 in comparison of other anthropometric measurements. Conclusions: Body mass index can be used for screening of obesity among geriatrics. however, body mass index should not be used to replace the other anthropometric measurements.